Selecting Reference Countries in External Reference Based Pricing: The Case Study of Iran: Selecting reference countries in external reference based pricing - Rahimi, Farimah; Rasekh, Hamid Reza; Abbasian, Ezatollah; Peiravian, Farzad (Iranian Journal of Pharmaceutical Sciences, 2018)
Most countries are using some kinds of pharmaceutical policies, like external reference-based pricing, to control the costs of medicines. This policy could be implemented in different ways and there is no systematic method for selecting reference countries. In this study, we tried to identify and classify the factors affecting the selection of reference countries in Iran .Delphi method was employed to elicit experts’ opinion in pharmaceutical sector on the parameters affecting the choice of reference countries. Members of the panel were experts in the field of policymaking, manufacturing, distribution, and importation of medicines, insurance companies, and academics who were more familiar with the purpose of the research. Panels were run in three rounds. The results of this study reveal that the impact of pharmaceutical, economy, and health sectors characteristics has been more effective, in selecting reference countries. Health insurance coverage was the most important index among all the different sectors. Other important indexes included pharmaceutical pricing system, mechanism of drug registration, gross national income (GNI) per capita, health expenditure per capita, health expenditure (share of GDP) and the out-of-pocket health expenditure. To have an efficient pharmaceutical external reference-based pricing, it is important to select reference countries with more similar important parameters. Obviously, any change in these parameters has to be considered and adjusted during the time.